Propiedades psicométricas del cuestionario de autoregulación emocional adaptado para el Perú (ERQP) - Gargurevich, Rafael (2015)
It were studied the psychometric properties of the Emotional Self-regulation Questionnaire (ERQ, Gross & Thompson, 2003) adapted for Peru (ERQP). This Lennia Matos Correspondencia: rafael.gargurevich@gmail.com 192 + Traducción: Melissa Casas Azañedo Rev. Psicol. 12, 192-215, 2010 questionnaire evaluates two emotional self-regulation strategies: the cognitive reappraisal and the suppression. The ERQP was applied to a sample of 320 university both sexes students from two private university. After making the linguistic adaptation of the questionnaire, it were studied the instrument construct validity. The Confirmatory Factor Analysis demonstrates the bivariate structure of the scale, and it was proved the convergent and divergent validity of the questionnaire. In index internal consistency Cronbach's Alpha both scales were 0.72 for cognitive reappraisal and 0.74 for suppression. It were discussed the importance of having an instrument which evaluates various strategies of emotional self-regulation because of the significance of this psychological phenomenon in people lives